Structural interdependence and economic development: proceedings of an international conference on input-output techniques, Geneva, September 1961 - Barna, Tibor; United Nations; Harvard University (London: Macmillan, 1963)
The papers brought together in this book were presented at the third International Input-Output Conference held in September in 1961 in Geneva.
occ 17/01/2019
Loans
Keywords: Input-output analysis; Economic development